Miasta zdegradowane w województwie lubuskim = Degraded towns in the lubuskie voievodship - Sokołowski, Dariusz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of this study is to characterize the towns degraded in the Lubuskie Voievodship from the historical, geographical, residential, economic-functional, and morphological aspects. Numerous sources of a historical, statistical and cartographic character, satellite pictures, and the results of field studies were used in the article. In the last part of the study, the author attempts to identify towns with the potential, i.e. formally rural settlements with a chance to regain their urban status.
Keywords: miasta zdegradowane; miasta potencjalne; prawa miejskie; morfogeneza miast; województwo lubuskie; degraded towns; towns with potential; urban rights; morphogenesis of towns; Lubuskie voivodship